How Much Do Soil and Water Contribute to the Composition of Meat? A Case Study: Meat from Three Areas of Argentina - Baroni, María Verónica (2011)
The main goal of this study was to propose a reliable method to verify the geographical origin of meat, establishing the influence of soil and water on its isotopic and elemental composition. Thus, beef meat, soil, and water samples were collected from three major cattle-producing regions of Argentina (Buenos Aires, C ordoba, and Entre Ríos). Multielemental composition was determined on these three matrices by inductively coupled plasma mass spectrometry (ICP-MS), δ13C and δ15N by isotope-ratio mass spectrometry (IRMS), and the 87Sr/86Sr ratio by thermal ionization mass spectrometry (TIMS). Soil and drinking water samples could be characterized and clearly differentiated by combining the isotopic ratios and elements, demonstrating differences in geology and climatic conditions of three regions. Similarly, meat originating at each sampling area was characterized and differentiated using only five key variables (Rb, Ca/Sr, δ13C, δ15N, and 87Sr/86Sr). Generalized procrustes analysis (GPA), using the three studied matrices (soil, water, and meat) shows consensus between them and clear differences between studied areas. Furthermore, canonical correlation analysis (CCA) demonstrates significant correlation between the chemical-isotopic profile of meat with those corresponding to both soil and water (r 2 = 0.93, p < 0.001; and r 2 = 0.83, p < 0.001, respectively). So far, there are clear coincidences between the meat fingerprint and those from soil/water where cattle grew, presenting a good method to establish beef provenance. To the authors' knowledge this is the first report linking the influence of soil and water all together on the composition of beef, presenting the basis for the authentication of Argentinean beef, which could be extended to meat from different provenances.